Water-Rock Interaction During CO2 Sequestration in Basalt - Flaathen, Therese Kaarbø (2009)
The potential dangers with increased concentration of CO2 in the atmosphere, such as climate changes and sea level rise, have lead to an interest in CO2 sequestration in geological formations. The thermodynamically most stable way to store carbon is as carbonate minerals. Carbonate mineral formation, however, requires divalent cations originating from a non-carbonate source. One such source is basaltic rocks which contain high concentrations of Ca2+, Mg2+ and Fe2+. The potential for forming carbonate minerals through the injection of CO2 into basalt is under investigation in Iceland and several other places around the world. The aim of this thesis is to help optimize carbonate mineral precipitation in basalts during CO2 injection through a series of related field and laboratory studies. A detailed study of the chemical composition of the groundwater surrounding the Mt. Hekla volcano in south Iceland was performed to assess fluid evolution and toxic metal mobility during CO2-rich fluid basalt interaction. These fluids provide a natural analogue for evaluating the consequences of CO2 sequestration in basalt. The concentration of dissolved inorganic carbon in these groundwaters decreases from 3.88 to 0.746 mmol/kg with increasing basalt dissolution while the pH increases from 6.9 to 9.2. This observation provides direct evidence of the potential for basalt dissolution to sequester CO2. The concentrations of toxic metals in these waters are low and reaction path modeling suggests that calcite and Fe(III) (oxy)hydroxides scavenge these metals as the fluid phase is neutralized by further basalt dissolution. The rate limiting step for mineralization of CO2 in basalt is thought to be the release of divalent cations to solution through basaltic glass dissolution. The dissolution rate of basaltic glass can be increased by adding ligands which complex aqueous Al3+. Aqueous SO42- can complex Al3+ and the effect of SO42- on the dissolution rate of basaltic glass was studied using mixed flow reactors at 3 < pH < 10 at ...